Pathways to motherhood: A single-center retrospective study on fertility preservation and reproductive outcomes in patients with breast cancer - Chao-Ying Chen; Yu-Chiao Yi; Hwa-Fen Guu; Ya-Fang Chen; Hsiao-Fan Kung; Jui-Chun Chang; Li-Yu Chen; Chih-Chiang Hung; Ming-Jer Chen (Journal of the Formosan Medical Association)
Background: Breast cancer treatments often have negative effects on fertility, which pose challenges among patients who want to be parents in the future. This study aimed to examine the efficacy of oocyte cryopreservation, embryo cryopreservation, and ovarian tissue cryopreservation in patients with breast cancer. Methods: This retrospective review evaluated 42 patients with breast cancer who underwent fertility preservation at our center from January 2012 to December 2022. This review encompassed the demographic characteristics of the patients, cancer stages, treatment details, and types of fertility preservation procedures and their outcomes. Results: The average age at disease diagnosis was 33.4 years. Approximately 90.4% of patients presented with early-stage cancer (≤2). Of 42 patients, 26 underwent oocyte cryopreservation; 17, embryo cryopreservation; and 2, ovarian tissue cryopreservation. Further, three patients received mixed treatment. The overall live birth rate was 63.2%. There are more live births in embryo cryopreservation group. The successful pregnancy group was significantly younger and had a remarkably higher quantity of preserved oocytes/embryos than the nonsuccessful pregnancy group. The oocyte and embryo utilization rates in cryopreservation were 7.69% and 52.94%, respectively. These findings underscored the importance of prompt, informed discussions about fertility preservation options. Conclusion: Fertility preservation in patients with breast cancer have promising reproductive outcomes, with embryo cryopreservation being particularly effective. Prompt counseling and individualized fertility preservation strategies are important for improving the likelihood of posttreatment pregnancy. Nevertheless, future research on the long-term psychological and emotional effects of different fertility preservation methods must be performed.